PENGARUH AUDIT TENURE, PROFITABILITAS, FINANCIAL DISTRESS TERHADAP AUDIT REPORT LAG DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Tri Nurwidayanti; Andy Dwi Bayu Bawono (JURNAL ILMIAH EDUNOMIKA, 2024)
The study aims to examine the influence of audit tenure, profitability, and financial difficulty on the duration of audit report lag, while also considering the moderating role of the audit committee. The present study employs a quantitative research approach, utilizing secondary data analysis to examine the population of manufacturing companies listed on the IDX during the period of 2019-2021. The data collecting process involves purposeful sampling of information from annual financial statements obtained from the BEI or from companies registered on the web. The total number of samples is 372. The study employed double regression analysis and MRA utilizing SPS version 23.0 as the data analysis approach. The findings of the conducted test indicate that there is no significant impact of tenure and financial hardship audits on audit report lag. However, it is observed that profitability has a detrimental effect on auditing report lag. The moderating role of the audit committee in the relationship between audit tenure, profitability, financial difficulty, and audit report latency is limited. Keywords: audit tenure, profitability, financial distress, audit report lag, audit committee.